Epigenetic Activation and Silencing of the Gene that Encodes IFN-γ - Aune, Thomas M.; Collins, Patrick L.; Collier, Sarah P.; Henderson, Melodie A.; Chang, Shaojing (Frontiers in Immunology, 2013)
Transcriptional activation and repression of genes that are developmentally regulated or exhibit cell-type specific expression patterns is largely achieved by modifying the chromatin template at a gene locus. Complex formation of stable epigenetic histone marks, loss or gain of DNA methylation, alterations in chromosome conformation, and specific utilization of both proximal and distal transcriptional enhancers and repressors all contribute to this process. In addition, long noncoding RNAs are a new species of regulatory RNAs that either positively or negatively regulate transcription of target gene loci. IFN-γ is a pro-inflammatory cytokine with critical functions in both innate and adaptive arms of the immune. This review focuses on our current understanding of how the chromatin template is modified at the IFNG locus during developmental processes leading to its transcriptional activation and silencing.